Cellulose oxygen isotopes of core BKB-2 over the past 2,000 years - Masanobu Yamamoto (PANGAEA, 2021)
The cellulose δ18O of plant tissues in peat is a potential climate proxy. However, understanding what is driving the shifts in δ18O of cellulose is required for its application. Here, we analyzed the δ18O values of Sphagnum and vascular plant cellulose, as well as the δ18O and δD values of pore water, in a 4-m-long peat core from the Bekanbeushi ombrotrophic bog to understand paleoclimatic changes in northern Japan over the past 2000 years. The cellulose δ18O values of Sphagnum were lower than those of vascular plant tissues, although both draw water from the same layer. Whereas the cellulose δ18O values of Sphagnum more directly reflect those of precipitation, those of vascular plants become enriched through transpiration. Thus, the difference between vascular plants and Sphagnum (Δδ18Ovp–sp) is a potential proxy for relative humidity. Cellulose δ18O of Sphagnum revealed centennial variations with maxima around 800, 1300, and 1500 CE and minima around 500, 1000, 1700, and 1900 CE. The Δδ18Ovp–sp was inversely correlated with Sphagnum cellulose δ18O, indicating that the axis of summer westerlies was more frequently located to the north and the climate was moist in the former periods, whereas the axis of summer westerlies was generally located to the south and the climate was dry in the latter periods. These results suggest a warm and moist climate during the former periods due to frequent rainy summers driven by strong East Asian summer monsoon activity, and the opposite conditions in the latter periods.